User-side cloud service management: State-of-the-art and future directions. (September 2015) - Rehman, Zia-ur; Hussain, Omar Khadeer; Hussain, Farookh Khadeer
Abstract: Cloud computing is increasing in usage because of its technical and financial advantages over traditional computing paradigms and also because of the availability of an expanding number of cloud services offered by new service providers. Consistent with its growth, there has been wide research interest in the literature that focuses on increasing cloud adoption. However, the current commercial and research-oriented cloud computing research in the literature mainly deals with functionalities closer to cloud infrastructure, such as improved performance and the management of virtualized resources, as well as fundamental issues related to efficient resource utilization, such as virtual machine (VM) migrations and server consolidation. While on the one hand, such features are very important, on the other hand, other important features, such as cloud quality of service management which is important for the cloud environment to move from a basic cloud service infrastructure to a broader cloud service ecosystem, have not received the required due attention. In cloud service management, a cloud service user has several choices for service selection and the quest to achieve interoperability and compatibility in cloud computing will consequently enable the user to easily migrate between service providers. In this scenario, the user needs to make important cloud service management decisions based on QoS, in addition to other criteria such as usage cost. These issues, when considered from a user׳s perspective, are quite different from cloud infrastructure management issues envisioned from a cloud provider׳s perspective. There are several challenges in cloud service management from a user׳s perspective, which the current cloud service management platforms in the literature do not address. To address this drawback, this paper presents a comprehensive state-of-the-art discussion on the existing approaches to cloud service management, critically evaluates them against the factors required for the user to manage the cloud service and presents a framework that assists the cloud service user in making cloud service management decisions.